Impact of post stroke depression and anxiety on health-related quality of life in young Filipino adults - Ignacio, Katrina Hannah D.; Medrano, Jose Miguel M.; Salabi, Sitti Khadija U.; Logronio, Alvin J.; Factor, Sedric John V.; Ignacio, Sharon D.; Pascual, Jose Leonard R.; Pineda-Franks, Maria Carissa; Diestro, Jose Danilo B. (Frontiers in Stroke, 2023)
Background: Health-related quality of life (HRQoL) is important to assess in young adults who suffer from various physical and mental consequences after stroke. We aimed to evaluate the HRQoL of young adults after ischemic or hemorrhagic stroke and to determine the association of anxiety and depression with poor HRQoL in this special population. Methods: We administered the EQ-5D-5L (European Quality of Life Five Dimension Five Level Scale) to assess the HRQoL in our study population. This tool describes health outcomes in five dimensions. Socio-demographic and clinical data including modified Rankin scale (mRS), Barthel Index and Hospital Anxiety and Depression Scale scores were available from our previous cross-sectional study on young adults with stroke. We performed bivariate analyses to assess the association of psychiatric comorbidities with categorical characteristics and determined risk factors for poor HRQoL using multivariable logistic regression analysis. Results: We evaluated HRQoL, psychiatric and functional outcomes in 114 young adult stroke patients. CVD infarct was more common than hemorrhage (58.8% vs 41.2%) Patients with both anxiety and depression were found to have the lowest ratings on the HRQoL scales, with an EQ VAS of 60 vs 90 (p 0.01) and an EQ Index of 0.64 vs 0.89 (p<0.01) when compared to those without both conditions. Anxiety and depression were significantly correlated with poor quality of life on all dimensions of the EQ-5D-5L. Similarly, Barthel Index was a significant predictor for problems in HRQoL (OR 0.17, 95% CI 0.03-1.02 on the mobility dimension and OR 0.08, 95% CI 0.01-0.55 on the self-care dimension). Cerebral hemorrhage was an independent predictor for poorer self-care dimension scores (OR 4.99, 95% CI 1.42-17.56). Conclusions: Our study showed that anxiety, depression and poor functional status are associated with poorer HRQoL in young adult Filipinos after stroke. Screening for psychiatric conditions and evaluating mobility are crucial in the management of this special population after stroke.